Normalisasi Hubungan Uni Emirat Arab-Israel dan Dampaknya Terhadap Palestina - Billah, Baedt Giri Mukhoddam; Hakim, Moh. Junaidi Mohtar; Bahruddin, Uril (Jurnal ICMES, 2023)
Normalizing relations between the United Arab Emirates (UAE) and Israel is a new history for the Arab World-Israel connection. The normalization agreement, the Abraham Accord, occurred in 2020 with the mediator of the President of the United States, Donald Trump. This study aims to map the forms of normalization of the UAE-Israel, the factors that support normalization, and their impact on Palestine. This study uses a qualitative method by coding and analyzing online news using various related literature. This study's results show three forms of normalization between the UAE and Israel: diplomatic by opening embassies and visa exemptions, tourism, and trade-economic; two factors driving normalization, namely economic and ideological factors. The impact of normalization for Palestine is to further weaken the solidarity of the Arab world in helping Palestine achieve independence from Israeli occupation